Two-dimensional speckle tracking of the ascending aorta: a novel approach to evaluate arterial stiffness in pediatric patients with repaired conotruncal anomalies using echocardiography - Goyal, Anmol; Parthiban, Anitha; White, David A.; Forsha, Daniel; Aly, Doaa (Frontiers in Cardiovascular Medicine, 2025)
BackgroundChildren with repaired conotruncal abnormalities (CTA) are at risk of progressive aortic dilation and deteriorating aortic elasticity even after surgical correction. Strain imaging, using a 2-dimensional speckle tracking echocardiography (2D-STE), has been used for arterial stiffness assessment, but pediatric data are still lacking. We investigated the feasibility, reproducibility, and clinical value of 2D-STE derived ascending aorta (AAo) stiffness in children with repaired CTA.Methods22 pediatric patients with repaired CTA were included along with 25 age- and sex- matched healthy controls (mean age 10.2 ± 4.5 years). Conventional 2D echocardiographic and 2D-STE assessment of AAo mechanics was performed. M-mode AAo strain, aortic distensibility and aortic stiffness index as well as 2D-STE derived AAo global circumferential strain (GCS) were calculated and compared between groups.Results2D-STE was successfully performed and analyzed in the entire, prospectively enrolled cohort. Patients with repaired CTA had significantly lower 2D-STE derived AAo GCS compared to controls (9.4 ± 1.3 vs. 15.2 ± 1.7, P-value <0.001). AAo GCS in repaired CTA patients had strong negative correlation with age (r = −0.76, CI −0.9 to −0.51) and a moderate negative correlation with the absolute aortic valve annulus (r = −0.55), absolute aortic root (r = −0.67), absolute sino-tubular junction (r = −0.67) and absolute AAo dimension (r = −0.71). On multivariate analysis, absolute aortic root and ascending aorta dimension were significantly associated with AAo GCS independent of other variables. Intra-observer reproducibility was good to excellent for the CTA and entire cohort (ICC = 0.87 and 0.96 respectively), while inter-observer reproducibility was moderate for the CTA cohort 0.71 vs. 0.92 for the entire cohort.ConclusionAAo GCS using 2D STE is highly feasible and reproducible as well as provides novel insights into the aortic deformation mechanics in pediatric patients with repaired CTA, thus holds promise in longitudinal assessment and risk stratification of aortopathy-associated congenital heart disease patients.